(untitled) (Journal of the College of Basic Education, 2025)
This study aimed to evaluate the role of negotiation strategy as an educational tool in improving the achievement of sixth-grade female students in science. A multi-week educational experience was implemented in which a group of students were trained in negotiation skills and applied to solve scientific problems related to the subject. Data were collected through assessment tests before and after the educational intervention to evaluate the effect of the negotiation strategy on student achievement. The results showed a significant improvement in students’ performance and achievement after training on negotiation, which indicates the effectiveness of this strategy as an educational tool in improving students’ performance in science, especially at the primary level. The research sample consisted of (65) female students. The researcher took into account some variables that could have an impact on the results of the experiment between the two groups. The results showed an increase in the experimental group’s scores.